Application of fuzzy cellular automata to optimize a vessel route considering the forecasted hydrometeorological conditions - Dudchenko, Sergiy; Tymochko, Oleksandr; Makarchuk, Dmytro; Golovan, Andrii (Eastern-European Journal of Enterprise Technologies, 2024)
The object of research is the processes of planning the minimum operating costs of a vessel with minimal risk to it and its cargo, considering the forecasted hydrometeorological conditions. The aim is to increase the fuel efficiency of a vessel’s passage, considering the forecast of weather conditions when forming an optimal safe route in the e-Navigation system. To achieve the research goal, conventional cellular automata and the mathematical apparatus of fuzzy sets and fuzzy logic were used in the process of decision-making and assessment of the impact of weather conditions on traffic efficiency. The devised approach makes it possible to synthesize an optimal route for the vessel, which ensures minimum fuel consumption and has minimal risk for the vessel and cargo while considering variable hydrometeorological conditions along the route. Minimization of operating costs is achieved through the ability of cellular automata to describe the complex behavior of objects, considering local rules. Automata are a computing system in discrete spaces. Data uncertainty has led to the need to use a fuzzy system, the effectiveness of which depends on the quality and accuracy of rules. Fuzzy automata, by combining fuzzy logic and automata theory, made it possible to process continuous steps and model the inherent uncertainty. To determine the state of cells of a fuzzy cellular automaton and the transition function between them, a system of productive rules and membership functions was used. It is the consistency of the system of productive rules when using fuzzy logic to build a cellular automaton that enables the construction of a quasi-global optimal routing method in comparison with conventional methods for calculating the ship’s route